Modeling of a Turbine Operating According to the Rankine Cycle and the Selection of the Optimal Working Fluid for it - جابر ديبة,; علا جلقمة, (Latakia University Journal -Engineering Sciences Series, 2022)
This study was conducted in order to generate electric power with small capacities based on solar energy, especially in remote places far from the electricity grid. Where this study includes an analytical study of a small steam turbine that operates on environmentally friendly low-temperature liquid vapor generated by solar energy. The theoretical performance as well as the thermodynamic and environmental properties of a few coolant fluids have been evaluated for use in low-temperature solar organic Rankine cycle systems. The effect of entry pressure, entry angle and entry temperature to the circuit was studied. R22-R134a-R513A environmentally friendly working fluids of type A1 were selected, then we mathematically modeled these fluids using the EES program, and it was found that the R513A working fluid has a higher efficiency compared to R134a and R22 and so that it is the most suitable for small solar energy applications.